Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
bao quynh Cao

 tính A =\(\frac{1}{1.2.3}+\frac{1}{2.3.4}+\frac{1}{3.4.5}+...\frac{1}{48.49.50}\)

 

Thanh Tùng DZ
24 tháng 5 2018 lúc 6:59

\(A=\frac{1}{1.2.3}+\frac{1}{2.3.4}+\frac{1}{3.4.5}+...+\frac{1}{48.49.50}\)

\(A=\frac{1}{2}.\left(\frac{1}{1.2}-\frac{1}{2.3}\right)+\frac{1}{2}.\left(\frac{1}{2.3}-\frac{1}{3.4}\right)+...+\frac{1}{2}.\left(\frac{1}{48.49}-\frac{1}{49.50}\right)\)

\(A=\frac{1}{2}.\left(\frac{1}{1.2}-\frac{1}{2.3}+\frac{1}{2.3}-\frac{1}{3.4}+...+\frac{1}{48.49}-\frac{1}{49.50}\right)\)

\(A=\frac{1}{2}.\left(\frac{1}{1.2}-\frac{1}{49.50}\right)\)

\(A=\frac{1}{2}.\left(\frac{1}{2}-\frac{1}{2450}\right)\)

\(A=\frac{1}{2}.\frac{612}{1225}=\frac{306}{1225}\)

Darlingg🥝
9 tháng 8 2019 lúc 17:37

\(A=\frac{1}{2}.\left(\frac{1}{1.2}-\frac{1}{1.3}\right)+\frac{1}{2}.\left(\frac{1}{2.3}\right)-\frac{1}{3.4}+...\frac{1}{2}\left(\frac{1}{48.49}\right)\)

\(A=\frac{1}{2}.\left(\frac{1}{2}-\frac{1}{6}+\frac{1}{6}-\frac{1}{12}+...\frac{1}{48.49}-\frac{1}{49.50}\right)\)

\(A=\left(\frac{1}{2}.\frac{1}{49.50}\right)\)

\(A=\frac{1}{2}.\left(\frac{1}{2}-\frac{1}{2450}\right)=\frac{1}{2}.\frac{1}{1225}=\frac{306}{1225}\)


Các câu hỏi tương tự
xamcon
Xem chi tiết
Minfire
Xem chi tiết
scotty
Xem chi tiết
Lê Ngọc Anh
Xem chi tiết
Nguyen Thuy Tien
Xem chi tiết
Ác Quỷ đội lốt Thiên Sứ
Xem chi tiết
Phạm Hải Yến
Xem chi tiết
Đào Thị Xuân Mỹ(Bé
Xem chi tiết
Vũ Minh Tâm
Xem chi tiết